Visualizing Listening: The Power of Mind Mapping through YouTube channel in Pesantren Higher Education at STIT Madani Yogyakarta - Dhian Marita Sari (English Teaching Journal : A Journal of English Literature, Language and Education, 2024)
The purpose of this study was to illustrate how visual tools for learning can be used to teach listening. Due to the teacher's lack of variety in the teaching approach, many students struggled to understand the overall idea, specific details, and inference. When teaching listening, the instructor needs to be adept at selecting engaging teaching tools. The main mapping was one of the visual learning tools since it had the potential to add excitement to the learning process. This research was both descriptive and quantitative. The 73 second-semester students from STIT Madani Yogyakarta served as the research subjects. An observation guide and a questionnaire were employed in this study to gather data, which were subsequently subjected to descriptive quantitative analysis and percentage calculations. The examination of observational data revealed that the main mapping as a visual tool for teaching listening increased student engagement and made the lesson enjoyable. Strong support for using YouTube with the main mapping to teach listening was observed in the study, which involved 73 students. 83.8% said it was simpler to absorb complex information, and 84.9% felt it helped identify important information. Main mapping enhanced learning retention, according to 63% of respondents. Main mapping made elaborating ideas easier for 97.16% of respondents, and 98.6% said it made listening lessons in the classroom more successful. The students felt more delighted, engaged, and passionate, and it was easier to assist their listening comprehension throughout the learning process.